Diagnosis & Management of Iron Deficiency Anemia via Parental Iron - Iqbal, MS; Ahmed, MS; Ogras, TT; Ullah, S; Asif, JH; Keshavarzi, F (International Journal of Natural Sciences, 2012)
All living things contain liquid inside their bodies which serves many functions like blood act as important connective tissue in transport of oxygen to all the cells similarly to excrete all the waste material from the cell to outside the body. Blood cells contain a red colored pigment which is called hemoglobin and its central portion is iron, when the level of haemoglobin falls in the body this condition is called anemia. To find the actual type of anemia different types of blood tests are conducted a person suffers. Most of the pregnant women suffer with the deficiency of iron. A study of such patients was conducted in Khyber Teaching Hospital Peshawar, and after collection of blood sample their test report indicate that most of the women were suffered with iron deficiency anemia. Total of seventy were taken into 2 groups A (n=40) and B (n=30). For iron deficiency anemia intravenous and intra muscular iron therapy was compared based on Hemoglobin (Hb) level Group A received intra venous iron (2 ampoules/alternate day), while Group B received intra muscular iron (1 ampoules/day). The data was recorded for group A (Hb=8.0±1.1 g/dl) at 15 days interval whereas for group B (Hb=8.8±0.9 g/dl) once prior to delivery. Group A showed an average rise of hemoglobin 2.5 g/dl with mean value of 10.8 g/dl. On the other hand Group B indicated an increase of hemoglobin 1.4 g/dl with mean of 10.2 g/dl target hemoglobin level (11 g/dl) was achieved 87% in group A and only 25% by group B. It was concluded that Intravenous therapy was safe, convenient and more effective than intramuscular iron therapy, in treating iron deficiency anemia. International Journal of Natural Sciences (2012), 2(3):88-90 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12138